Strategi Public Relations Brand Le Havre - Tanasia, Valen; Aulia, Sisca (Prologia, 2023)
Le Havre (PT Lingkaran Delapan Emas) is a company founded in 2017 by Karina Gani. Focusing on home fragrance products such as reed diffuser and room & linen spray. The purpose of this thesis research is to explain the public relations strategy carried out by the Le Havre brand and explain the efforts and processes of the public relations strategy for the Le Havre brand, especially at the Kumulo bazaar. This thesis research uses several concepts, namely public relations, and public relations Strategy. The author uses a case study research method. The subject of this thesis research is the public relations of the Le Havre brand. The object of this thesis research is the public relations strategy carried out by the Le Havre brand at the Kumulo bazaar. The method of collecting data for this thesis research is through interviews, observation, and documentation. Public Relations activities carried out by the Le Havre brand are related to the public relations strategy from process to evaluation. The public relations strategy includes publications, events, news, community involvement, information of image, lobbying and negotiation, and social responsibility or social activities as a form of caring for the environment. The findings from the public relations strategy for the Le Havre brand indicate that the public relations for the Le Havre brand have already carried out planning and programming before taking action. The planning and program ran smoothly but the results of the planning and program were ultimately unsatisfactory. After negotiating with Kumulo, the response from Kumulo was quite disappointing so Le Havre decided not to participate in the Kumulo Bazaar anymore. Le Havre (PT Lingkaran Delapan Emas) merupakan perusahaan yang berdiri pada tahun 2017 oleh Karina Gani. Berfokus pada produk wewangian rumah seperti reed diffuser dan room & linen spray. Tujuan penelitian skripsi ini adalah untuk menjelaskan strategi public relations yang dilakukan oleh brand Le Havre dan menjelaskan upaya serta proses dari strategi public relations pada brand Le Havre khususnya di Bazar Kumulo. Penelitian skripsi ini menggunakan beberapa konsep yaitu public relations dan strategi public relations. Penulis menggunakan metode penelitian studi kasus. Subjek dari penelitian skripsi ini merupakan public relations dari brand Le Havre. Objek dari penelitian skripsi ini merupakan strategi public relations yang dilakukan oleh brand Le Havre di Bazar Kumulo. Metode pengumpulan data penelitian skripsi ini merupakan melalui wawancara, observasi, dan dokumentasi. Aktivitas public relations yang dilakukan oleh brand Le Havre berkaitan dengan strategi public relations dari proses hingga evaluasi. Strategi public relations tersebut mencakup publications (publikasi), event (acara), news (berita), community involvement (komunitas), inform of image (citra), lobbying and negotiation (lobi dan negosiasi), dan social responsibility (kegiatan sosial sebagai bentuk peduli terhadap lingkungan). Hasil temuan dari strategi public relations pada brand Le Havre menunjukkan bahwa public relations pada brand Le Havre sudah melakukan perencanaan dan program sebelum mengambil tindakan. Perencanaan dan program tersebut berjalan dengan lancar namun hasil dari perencanaan dan program tersebut pada akhirnya kurang memuaskan. Setelah melakukan negosiasi dengan pihak Kumulo, respon dari pihak Kumulo pun terbilang sangat mengecewakan maka Le Havre memutuskan untuk tidak mengikuti Bazar Kumulo lagi.